Mammary Paget's Disease of Young Females: Case Reports and Comparison With Middle-Aged and Elderly Patients - Chun-yan Lv; Xian-kui Cheng; Zhong-Yue Guo; Li Liu; Jian Cai; Tao Lei; Yan Tang (SAGE Publishing, 2023)
Purpose: Mammary Paget's disease (PD) in young women has seldom been reported. The aim of this study was to improve the knowledge of the clinicopathological characteristics in young patients with PD to provide a basis for the precise treatment of young patients. Methods: The medical records and pathological slides of 8 young patients (younger than 40 years old) with PD were reviewed. The data of 20 patients over 40 years old within the same period were used as controls. Results: The average age was 32.00 ± 3.96 years for the young patient group, with the youngest aged 27 years. The first symptom, physical examination, Paget cell morphology, and immunohistochemical marks were the same in different age groups. But young patients have varied tumor distribution patterns, fewer interstitial inflammatory cells, and advanced pathological local lymphatic metastasis than older patients in the same period. Conclusions: PD in young women has unique histopathological features. These manifestations seem to provide personalized treatment for PD treatment in young patients. More research is needed to clarify the significance of this research.